Mass attitudes toward financial crisis and economic reform in Korea - Bernd Hayo (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2005)
This paper gives an account of the financial crisis that took place in Korea from the point of view of the Korean population using survey data collected in 1998 and 1999. Although both, internal and external factors were blamed as causes, domestic factors were considered to be of greater importance. After identifying respondents as supporting either market-based or statebased reform strategies using factor analysis, various determinants of these alternative views are being analyzed within the framework of regression models. A particularly interesting result is that, contrary to theoretical assumptions and empirical evidence on other regions, it is political ideology and not individual economic determinants that helps to explain the respondents attitudes towards reform strategies in Korea.
Keywords: O5; F3; 330; South Korea; financial crisis; public opinion; economic reform strategies institution; Öffentliche Meinung; Wirtschaftsreform; Public Choice; Südkorea; Finanzmarktkrise